2016
DOI: 10.1186/s12887-016-0672-0
|View full text |Cite
|
Sign up to set email alerts
|

Are Chinese pediatricians missing the opportunity to help parents quit smoking?

Abstract: BackgroundSecondhand smoke (SHS) exposure of children due to parental tobacco use is a particularly prevalent health issue and is associated with adverse health outcomes. Following the US Clinical Practice guidelines, pediatricians in the United States deliver 5A’s (ask, advise, assess, assist, and arrange) counseling to smoking parents which has proven to be effective. We examined Chinese pediatricians’ adherence to the clinical practice guidelines for smoking cessation (i.e. 5A’s counseling practices) with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Smokers with a history of 24 h of abstinence in the past year and those who have tried more methods of stopping smoking are more likely to achieve a longer quit period in smoking cessation programs [36]. Given that only 22.4% of pediatricians in China regularly advise parents to quit smoking and that only 3.8% of pediatricians arrange a follow-up appointment to assess the effects of their advice [37], it might be practical for community health workers and nurses in China to provide smoking cessation services. However, a lack of training in reducing tobacco consumption and in cessation counseling is a primary barrier to the provision of SHS exposure reduction services by pediatric nurses [38].…”
Section: Discussionmentioning
confidence: 99%
“…Smokers with a history of 24 h of abstinence in the past year and those who have tried more methods of stopping smoking are more likely to achieve a longer quit period in smoking cessation programs [36]. Given that only 22.4% of pediatricians in China regularly advise parents to quit smoking and that only 3.8% of pediatricians arrange a follow-up appointment to assess the effects of their advice [37], it might be practical for community health workers and nurses in China to provide smoking cessation services. However, a lack of training in reducing tobacco consumption and in cessation counseling is a primary barrier to the provision of SHS exposure reduction services by pediatric nurses [38].…”
Section: Discussionmentioning
confidence: 99%
“…This model has shown to be an effective way to help patients to quit smoking in primary care outpatient settings in most of the developed countries [22,23]. To our knowledge, few studies have reported the use of WHO-5A model in developing countries [24]. It has not yet been used in non-medical workplaces and its application and effectiveness among Chinese migrant workers are unknown.…”
Section: Introductionmentioning
confidence: 99%